GAMBARAN KEBIASAAN MAKAN DAN FAKTOR EKOLOGI WANITA USIA SUBUR DI KECAMATAN SIDEMEN KABUPATEN KARANGASEM BALI - Jaya Putra, I Putu Okta Diwian; Utami, Ni Wayan Arya (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2023)
Women of Reproductive Age (WUS) are one of the high-risk groups for anemia. Anemia in WUS is caused by direct factors (nutritional intake and infectious diseases) and indirect factors (ecological factors). Research on the ecological factors of the incidence of anemia in WUS in Bali is still lacking and the results vary. The purpose of this study was to describe the consumption habits and ecological factors of women of childbearing age (WUS) in Sidemen District, Karangasem Regency, Bali. This study is a descriptive study with a cross-sectional design conducted in Sidemen District, Karangasem Regency. The sample was selected by total sampling. The number of respondents who met the inclusion and exclusion criteria was 186 people. Ecological data factors were collected by interview using a structured questionnaire, while consumption pattern data was collected using a food frequency questionnaire (FFQ). Data were analyzed descriptively and presented narratively. The results of sociodemographic characteristics show that the majority of WUS are in the age group of 20-35 years (51.8%), graduated from SD/MI (46.7%), are self-employed (55.9%), and have income <UMK Kab. Karangasem (Rp 2,555,469.09) (93.5%). The most accessible sources of food, health facilities, and water sources are food stalls (99%), puskesmas (81.7%), and springs (51.4%). As many as 55.4% of WUS have never accessed information related to anemia, 68.2% WUS have less frequent protein consumption, and 82.3% eating habbits is not diverse Keywords: Ecological Factor, Women of Reproductive Age, Sidemen Regency